Anodic Polarization Characteristics and Electrochemical Properties of Fe3C in Chloride Solutions. Issue 12 (2nd August 2019) - Kadowaki, Mariko; Muto, Izumi; Takahashi, Kinari; Doi, Takashi; Masuda, Hiroyuki; Katayama, Hideki; Kawano, Kaori; Sugawara, Yu; Hara, Nobuyoshi
Abstract : The anodic polarization behavior of cementite (Fe3 C), which was prepared by gas carburizing, was investigated in 10 mM NaCl-containing boric-borate buffers with pH values of 6.0, 7.0 and 8.0. The active dissolution current of the Fe3 C was found to be lower than that of the ferrite. This suggests that the corrosion resistance of the Fe3 C was clearly higher than that of the ferrite. From the potential-pH diagrams, carbon was predicted to be generated on the Fe3 C at lower potentials during the anodic polarization, and the existence of carbon was confirmed by XPS. The carbon layer seems to act as a protective film and suppress the active dissolution of the Fe3 C at lower potentials. AES depth profiles clarified that iron oxide layers existed not only on the ferrite but also on the Fe3 C. The Volta potential of the Fe3 C was approximately 40 mV higher than that of the ferrite. The higher Volta potential of the Fe3 C layer seemed to be associated with the nature of the oxide film formed on the Fe3 C, and there is a possibility that the passivation of the Fe3 C at higher potentials is achieved by an oxide film.